Digitization of Audio Recordings on Phonograph Wax Cylinders “Koppers Feuerland”: Reseña de audio - Molina M., Joaquín J. A. (Notas de Antropología de las Américas, 2025)
Reseña de audio / Audio review: Digitization of Audio Recordings on Phonograph Wax Cylinders “Koppers Feuerland,” from the Museo Nacional de Historia Natural de Chile, by curator Francisco Garrido (2022) https://soundcloud.com/mnhncl/cilindro